آثار الاستثمار الأجنبي المباشر على النمو الاقتصادي: دراسة قياسية على دول مجلس التعاون الخليجي خلال الفترة 1990- 2014 - نسيمة جلولي; يوسف صوار (My University, 2016)
الهدف من هذه الورقة هو قياس أثر الاستثمار الأجنبي المباشر على النمو الاقتصادي لدول الخليج خلال الفترة 1990-2014، باستخدام تحليل الانحدار لبيانات مقطعية، تم تقدير النموذج المختار بناءا على بعض الاختبارات الإحصائية، وبتطبيق طريقة المربعات الصغرى ذات المرحلتين، حيث كشفت نتائج المرحلة الأولى عن ايجابية ومعنوية تأثير كل من FDI والصادرات على GDP، غير أن تأثير الصادرات هو أكثر فعالية، بينما أشارت نتائج المرحلة الثانية إلى سلبية ومعنوية تأثير FDI، وأن الآثار الايجابية لــFDI تعتمد على الانفتاح التجاري، الدخل الفردي وسعر الصرف المتوفرة بالدول المضيفة. Abstract: This paper aims to estimate the effect of Foreign Direct Investment (FDI) on economic growth (GDP) in Arab Gulf Countries, during the period 1990-2014, using regression model for panel data, the model chosen are estimated by some statistical procedures, the OLS method are used for tow step, our results in first step indicate that the FDI and export have a positive and significant impact on GDP, however, the impact of export is more efficient than FDI, when the results of second step indicate that FDI has a negative and significant impact on GDP, and the most robust finding of this paper is that the effect of FDI is dependent on the level of trade openness, per capita income, and exchange rate available in the host economy.
Keywords: الاستثمار الأجنبي المباشر، النمو الاقتصادي، دول الخليج